Reinterpretasi Konsep Bidah Menuju Islam Transformatif - Nanang Hasan Susanto (Jurnal Madania)
Reinterpretation the Concept of Heretic toward the Transformative of Islam. This articles aims to reinterpret the concept of heretic (bidah) with a philosophical approach, based on the concept of the transformative of Islam proposed by Moeslim Abdurrahman. The data were collected through library research of the whole concept of heresy, both conservative and moderate then analyzed based on the concept of the conceptual, sociological and antropological approach. This paper found the need to think philosophically about the concept of heretic, by finding the basic purpose of the revealed of religion, so that there is no contradiction between one doctrine and another. Thus, heresy is no longer as the burden of history of Muslim creativity and innovation, but it is indeed the impetus to find breakthroughs in the settlement of various social problems of society.